2014 IEEE 18th International Conference on Dielectric Liquids (ICDL) 2014
DOI: 10.1109/icdl.2014.6893127
|View full text |Cite
|
Sign up to set email alerts
|

High thermal conductivity transformer oil filled with BN nanoparticles

Abstract: Liquid insulation plays a significant role in the design and operation of power system. There is good evidence in the literature that the addition of nanoparticles to conventional transformer oils can lead to significant increases both in electrical and thermal characteristics. In this paper, spherical BN nanoparticles with high thermal conductivity were added into transformer oil to form nanofluids, with the aim of enhancing electrical and thermal properties. Electrical properties and thermal characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…% of h-BN nanosheets. Figure 6b shows relative comparison of performance of the nanofluids between the present work and that reported by Du et al [9]. The theoretical emphasis on the breakdown phenomena of the nanofluids has been clarified by statistical analysis using the Weibull distribution function [10], which for any random variable say "x" (BDV in the present study) is defined as [10]:…”
Section: Ac Breakdown Voltagementioning
confidence: 53%
See 3 more Smart Citations
“…% of h-BN nanosheets. Figure 6b shows relative comparison of performance of the nanofluids between the present work and that reported by Du et al [9]. The theoretical emphasis on the breakdown phenomena of the nanofluids has been clarified by statistical analysis using the Weibull distribution function [10], which for any random variable say "x" (BDV in the present study) is defined as [10]:…”
Section: Ac Breakdown Voltagementioning
confidence: 53%
“…The effect of interfacial layer in scavenging the free charges for spherical (particle) and 2D morphologies of the nanofillers are presented in Figure 8. Previously reported BN particle of 50 nm size [9] and presently used h-BN nanosheets (2D) have almost similar resistivity and conductivity. However, with the same volume fraction, 2D nanosheets of h-BN provide a huge area of the interfacial layer and high aspect ratio resulting into more trapping of free electrons and create noteworthy augmentation of BDV as compared to the spherical morphology of BN family, as furnished in Figure 6b.…”
Section: Ac Breakdown Voltagementioning
confidence: 82%
See 2 more Smart Citations
“…Recently, in the dielectric materials field, the usage of nanomaterial modification technology has been the research hotspot [1], [2], and it can be used to improve the electricity [3], [4], heat conduction [5], [6] and aging [7], [8] of insulation oil. Yuxiang Zhong and his team found that TiO 2 nanoparticles not only enhance the AC breakdown voltage of ester-based nanofluid, but also improve the partial discharge performance of ester-based nanofluids compared to natural esters [9].…”
Section: Introductionmentioning
confidence: 99%